1994
DOI: 10.1038/nsb0294-83
|View full text |Cite
|
Sign up to set email alerts
|

Human telomeric C–strand tetraplexes

Abstract: Telomeric C-strand sequences form non-Watson-Crick base-paired structures in supercoiled plasmids and in oligonucleotides at low pH. Here we examine oligonucleotides composed of 2 or 4 repeats of the human telomeric C-strand sequence d(CCCTAA)n. At low pH, the 2-repeat molecule forms a dimer which exhibits H1'-H1' nuclear Overhauser effects (NOEs) between stacked CC+ base pairs. These NOEs are characteristic of the i-motif, which is a tetraplex composed of two intercalated CC+ duplexes. The 4-repeat molecule f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 42 publications
3
92
0
2
Order By: Relevance
“…Depending on the length and nature of the guanine blocks, G4 DNA can involve either one, two, or four separate DNA strands. And if conditions are right, the displaced C-rich strand can fashion a structure known as the 'i-motif', which is a four-stranded structure composed of two intercalated, hemiprotonated, cytosine-cytosine base pairs [50]. Formation of H-and G 4 -DNA and i-motif structures could influence transcription in a number of ways, including preventing recognition by sequence-specific DNA-binding proteins, altering the distance or stereospecific alignment of promoter elements, or recruiting new factors that specifically recognize altered DNA configurations.…”
Section: Chromatin Control Through Changes In Dnamentioning
confidence: 99%
“…Depending on the length and nature of the guanine blocks, G4 DNA can involve either one, two, or four separate DNA strands. And if conditions are right, the displaced C-rich strand can fashion a structure known as the 'i-motif', which is a four-stranded structure composed of two intercalated, hemiprotonated, cytosine-cytosine base pairs [50]. Formation of H-and G 4 -DNA and i-motif structures could influence transcription in a number of ways, including preventing recognition by sequence-specific DNA-binding proteins, altering the distance or stereospecific alignment of promoter elements, or recruiting new factors that specifically recognize altered DNA configurations.…”
Section: Chromatin Control Through Changes In Dnamentioning
confidence: 99%
“…In multicellular animals, the C-rich strand repeating sequence is generally d(TAACCC). NMR studies of C-rich telomere sequences show that they can also form a four-stranded structure with cytosine-containing parallel duplexes held together by hemiprotonated (C C+) base pairs and two duplexes intercalated with each other in opposite polarity (8)(9)(10). Recent x-ray diffraction studies of C-rich deoxynucleotides have revealed many features of this intercalative system (11,12).…”
mentioning
confidence: 99%
“…These C-rich oligonucleotides form stable structures at low pH (Ahmed and Henderson, 1992;Ahmed, et al, 1994). Two dimensional NMR spectroscopy showed that these structures were C-tetraplexes (Ahmed, et al, 1994). In addition, electrophoresis experiments demonstrated that C-tetraplexes, like G-tetraplexes, could mediate recognition and binding between identical nucleic acid sequences (Ahmed, et al, 1994).…”
Section: Unusual Dna Structuresmentioning
confidence: 99%
“…We have examined the structural characteristics of oligonucleotides containing telomeric Cstrand sequences. These C-rich oligonucleotides form stable structures at low pH (Ahmed and Henderson, 1992;Ahmed, et al, 1994). Two dimensional NMR spectroscopy showed that these structures were C-tetraplexes (Ahmed, et al, 1994).…”
Section: Unusual Dna Structuresmentioning
confidence: 99%
See 1 more Smart Citation